Silence, Love, and Death: A Deconstructive Analysis of Michael and Marina Moonwater - Rifka, Hilyana Ainur (NOBEL: Journal of Literature and Language Teaching, 2026)
This study analyses Christopher Blaine's short story Michael and Marina Moonwater (2015) through Jacques Derrida's deconstructive theory. The short story depicts a relationship that has lasted for forty-six years and is based on silence, challenging the conventional assumption that love depends on understanding expressed through verbal communication. Derrida's concepts of différance and binary opposition are used to explore how silence, death, and love are present in unstable and contradictory meanings. This study applies a descriptive qualitative method with a focus on textual contradictions and the reversal of the hierarchy of meaning in the narrative. The results of the analysis show that the silence in Blaine's story can be interpreted as a form of the language of love, where absence gives birth to presence, implying that emotional understanding can be formed without the involvement of verbal language. This interpretation confirms that meaning in human relationships is fluid, never fixed, and always open to new interpretations.